Penyegaran Teknologi Untuk Penyuluh Dan Pelaku Usaha Perikanan - Pramono Adi (indoneisa), Catur; (Indonesia), Waluyo (Fakultas Pertanian_Universitas Tidar, 2024)
The goal of technology refresh initiatives is to spread awareness of suggested technological advancements, particularly those created by the Maritime and Fisheries Research and Development Agency. However, there is a disparity between the technological needs at the community level and the available technology in different regions. The extent of this disparity varies depending on the region's potential and the carrying capacity of its human resources. A number of inferences can be drawn, including: 1. According to the participants, this activity is very helpful for expanding knowledge, particularly in the area of technology, which serves as the basis for technical advise. With varying degrees of progress, participants' knowledge increased. Naturally, this has to do with the participants' varied educational and professional backgrounds (capture and aquaculture), as well as the potential of the fisheries in their respective regions and the range of information offered.